AN INQUIRY-BASED FRESHMAN BIOCHEMISTRY LAB SET TO ENHANCE STUDENTS' AUTONOMY - Silva, Thanuci [UNESP]; Galembeck, Eduardo [UNESP] (Soc Brasileira Quimica, 2017)
Inquiry-based laboratory sessions are recognized for contributing to enhancing students' autonomy and they were used in the reorganization of the Biochemistry laboratory offered to freshman Biology students in this university. Students were previously asked to follow rigid laboratory protocols attempting to achieve the correct results of their experiments. The inquiry-based activities were designed to develop students autonomy to plan and to perform experiments, as well as communicating and discussing their results. The inquiry-based and autonomy approach followed is classified in the literature as Organizational, Procedural, and Cognitive. The levels of autonomy required from students were increased sequentially. The first activity was the least demanding, since the students received detailed instructions from the worksheet. The activities became gradually more complex, transferring to students most decisions on setting up and performing the experiments. Student skill improvement was obtained, as verified by excerpts from student reports, by data obtained from content analysis of the exams, and scientific report scores indicate that this approach may have stimulated the improvement of several skills related to different autonomy aspects. Most important, students showed increased ownership of the laboratory materials, reagents, laboratory environment and especially of learning, showing a sense of active participation in the experimental activities.
Keywords: inquiry-based; biochemistry laboratory; autonomy